Types of clinical reasoning in a summative clerkship oral examination. (3rd June 2022) - Rajeswaran, Vamana; Devine, Luke; Lorens, Edmund; Robertson, Sumitra; Huszti, Ella; Panisko, Daniel M.
Abstract: Introduction: Dual-process theory characterizes clinical reasoning (CR) as Type 1 (intuitive) and Type 2 (analytical) thinking. This study examined CR on a summative clinical clerkship structured clinical oral examination (SCOE). Methods and subjects: 511 clinical clerks at the University of Toronto underwent SCOEs. Type 1, Type 2, and Global CR performance were compared to other internal medicine clerkship assessments using descriptive statistics and Spearman correlations. Results: Clinical clerks achieved mean marks >75% on the three clinical reasoning stations, on Type 1 and 2 CR tasks, and the overall SCOE. Performance on the SCOE CR stations correlated with each of the other clerkship assessments: written examination, inpatient, and ambulatory clinic assessments. The correlation of performance between Type 1 and Type 2 clinical reasoning tasks was statistically significant but weak ( rs = 0.28). This suggests that defined measures of Type 1 and Type 2 reasoning were indeed assessing distinct constructs. Conclusion: Clinical clerks used both Type 1 and Type 2 reasoning with success. This study's characterization of Type 1 and Type 2 CR as separate domains, distinct from existing measures on the SCOE as well as the other clerkship assessments, can suggest a further addition to multimodal clerkship assessment.